Description of Spiniola hanaro Park, gen. and sp. nov., and three new species of Torodora Meyrick, 1894 (Lepidoptera, Lecithoceridae, Torodorinae) from the Afrotropical Region - Park, Kyu-Tek; Koo, Jun-Mo (Zootaxa, 2022)
A new genus, Spiniola Park, gen. nov., is described from Malawi, based on the type species, S. hanaro Park, sp. nov., and three new species of Torodora Meyrick, 1894 are described: T. batillana Park & Koo, sp. nov. from Kenya, and T. chrysotes Park & Koo, sp. nov. and T. manalis Park & Koo, sp. nov. from Uganda. Images of adults and genitalia of the new species are provided.